Advances and clinical challenges of mesenchymal stem cell therapy - Mei, Ruiyan; Wan, Zhuo; Yang, Cheng; Shen, Xiangjing; Wang, Ronglin; Zhang, Haihua; Yang, Rui; Li, Junqiang; Song, Yang; Su, Haichuan (Frontiers in Immunology, 2024)
In recent years, cell therapy has provided desirable properties for promising new drugs. Mesenchymal stem cells are promising candidates for developing genetic engineering and drug delivery strategies due to their inherent properties, including immune regulation, homing ability and tumor tropism. The therapeutic potential of mesenchymal stem cells is being investigated for cancer therapy, inflammatory and fibrotic diseases, among others. Mesenchymal stem cells are attractive cellular carriers for synthetic nanoparticles for drug delivery due to their inherent homing ability. In this review, we comprehensively discuss the various genetic and non-genetic strategies of mesenchymal stem cells and their derivatives in drug delivery, tumor therapy, immune regulation, tissue regeneration and other fields. In addition, we discuss the current limitations of stem cell therapy and the challenges in clinical translation, aiming to identify important development areas and potential future directions.